2008
DOI: 10.1029/2007gl032459
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected rapid decrease in phase velocity of submeter Farley‐Buneman waves with altitude

Abstract: [1] An unexpected and drastic drop in the phase velocity V ph of Farley-Buneman (FB) waves with increasing altitude was observed in the equatorial electrojet over Jicamarca. The effect was detected with the newly employed 430-MHz radar looking vertically. The decrease in V ph was 67 m/s and 36 m/s over 2.4 km for the FB waves moving towards and away from the radar, respectively. By contrast, the 430-MHz data from 20°west displayed little dependence on altitude. Simultaneous observations with a 50-MHz radar at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, velocities of classical vertically propagating Type 1 echoes were smaller (380 m/s versus our 400–600 m/s) although larger velocities of 440–460 m/s have also been reported recently [ St.‐Maurice et al , 2003]. One should also note that a velocity decrease with height was reported for the vertically propagating Type 1 echoes at ∼ 50 MHz [ St.‐Maurice et al , 2003] and at 430 MHz [ Kagan et al , 2008], while in our case, if one assumes that the change in range within the E region echo band corresponds to the change in height, an opposite effect was observed.…”
Section: Discussionsupporting
confidence: 72%
“…However, velocities of classical vertically propagating Type 1 echoes were smaller (380 m/s versus our 400–600 m/s) although larger velocities of 440–460 m/s have also been reported recently [ St.‐Maurice et al , 2003]. One should also note that a velocity decrease with height was reported for the vertically propagating Type 1 echoes at ∼ 50 MHz [ St.‐Maurice et al , 2003] and at 430 MHz [ Kagan et al , 2008], while in our case, if one assumes that the change in range within the E region echo band corresponds to the change in height, an opposite effect was observed.…”
Section: Discussionsupporting
confidence: 72%
“…As shown by Kagan and Kissack [1] and Kagan et al [30], the threshold phase velocity of Farley-Buneman waves depends largely on three different parameters: (1) the magnetic aspect angle, (angle between the wave vector k and the plane perpendicular to the background magnetic field); (2) the flow angle, f (angle between k and the relative ion-electron drift u); and (3) the height of the backscatter, through the height dependence of collisional frequencies, electron temperature, and the inelastic electronneutral energy exchange rate. These three dependences each present problems when working with SuperDARN data, since neither the backscatter height nor the magnetic aspect angle are known, and there is very limited control over the flow angle.…”
Section: Theoretical Descriptionmentioning
confidence: 77%
“…Kagan et al [30] further advanced applications of the Kissack et al [23,24] theory by introducing two control parameters AT (for super-adiabatic) and T (for thermal conduction/diffusion) which define behavior of the FB wave. This in turn, allowed them to explain an unexpected and drastic drop in the phase velocity, V ph , of Farley-Buneman waves with increasing altitude observed in the equatorial electrojet over Jicamarca with the newly employed 430-MHz radar looking vertically.…”
Section: Introductionmentioning
confidence: 99%
“…This figure is not simply a static figure but depends on the ratios of specific heat for the electrons and ions, which in turn depend on the altitude of the waves and their wavelength, which is related to the wavelength of the probing radar [Farley and Providakes, 1989;St. Maurice et al, 2003;Hysell et al, 2007;Kagan et al, 2008]. Furthermore, wave heating can drastically modify the local electron temperature and the ion acoustic speed with it, particularly in the auroral zone [e.g., St. Maurice and Laher, 1985;St.…”
Section: Farley-buneman Gradient Drift Instabilitymentioning
confidence: 99%
“…Nevertheless, questions remain, particularly with regard to how FarleyBuneman waves propagate and saturate. A contemporary series of studies has demonstrated that the ion acoustic speed in the electrojet is not isothermal [St.-Maurice et al, 2003;Hysell et al, 2007;Kagan et al, 2008]. Two-dimensional kinetic simulations of Farley-Buneman waves described by Oppenheim et al [2008] and Dimant and Oppenheim [2008] recover many of the observed features of the waves, including their tendency to propagate with phase speeds below that predicted by linear theory.…”
Section: Introductionmentioning
confidence: 97%